The presence of both serotonin 1A receptor (HTR1A) and dopamine transporter (DAT1) gene variants increase the risk of borderline personality disorder - Joyce, Peter R.; Stephenson, John; Kennedy, Martin A.; Mulder, Roger T.; Mchugh, Patrick C. (Frontiers in Genetics, 2014)
Dysfunction in the dopaminergic and serotonergic neurotransmitter systems has been demonstrated to be important in the aetiology of Borderline personality disorder (BPD). We investigated the relationship of two BPD risk factors, the HTR1A promoter polymorphism -1019C>G (rs6295) and the DAT1 repeat allele, with BPD in a major depressive disorder cohort of 367 patients. Out-patients with major depressive disorder were recruited for two treatment trials and assessed for personality disorders, including BPD. DNA samples were collected and the rs6295 polymorphism was detected with a TaqMan® assay. The DAT1 repeat allele was genotyped using a modified PCR method. The impact of polymorphisms on BPD was statistically analysed using uncontrolled logistic and multiple logistic regression models. BPD patients had higher frequencies of the DAT1 9,9 (OR=2.67) and 9,10 (OR=3.67) genotypes and also those homozygous HTR1A G allele (OR=2.03). No significant interactions between HTR1A and DAT1 genotypes, were observed; however, an increased risk of BPD was observed for those patients who were either 9,10; G,G (OR=6.64) and 9,9; C,G (OR=5.42). Furthermore, the odds of BPD in patients exhibiting high-risk variants of these two genes differed from those of patients in low-risk groups by up to a factor of 9. Our study provides evidence implicating the importance of the serotonergic and dopaminergic systems in BPD and that the interaction between genes from different neurotransmitters may play a role in the susceptibility to BPD.